THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDES AND PARENTAL ROLES WITH READINESS TO FACE MENARCHE IN EARLY ADOLESCENTS - Sri, Nina; Purdianingsih, Sri (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Adolescents who are about to menstruate need good mental preparedness. Teenagers who are not ready to face menarche will feel menstruation as something cruel and threatening, this situation can continue into adulthood if they are not given the right information. The aim of the research was to determine the relationship between knowledge, attitudes and the role of parents with readiness to face menarche. This type of research is quantitative research with a descriptive analytical design and a cross sectional approach. The population in the study were all early teenage female students at SDN 01 Sukalarang, totaling 117 female students with a sample size of 100 respondents. The sampling technique uses quota sampling. The research was conducted in February 2024 using a questionnaire as a research instrument in collecting data which was analyzed using Chisquare. The results of the analysis showed that there was a relationship between knowledge (p-value= 0.005, OR= 3.727), attitude (p-value= 0.030, OR= 2.681), and the role of parents (p-value= 0.017, OR= 2.895) towards readiness to face menarche in early adolescents. The need to improve, optimize and develop health programs reproduction for early adolescents, especially in providing health education about menarche.